(untitled) (La Rivada, 2024)
In this paper we propose to analyze the social representations constructed about Senegalese migrants in two of in two of the main Argentinean’s print media outlets, from discourse analysis perspective. With this objective, we examine news articles that referred to this migrant population using the online archives of Clarín and Página 12, between 2001 and 2022, a period that also coincides with their stay in the country. The corpus consists of 91 articles in total, which, after being gridded, were analysed using Atlas.ti software. For this study we focused on the overall representations of the Senegalese population traceable from the ways in which they are discursively constructed through the use of naming and categorisations. The analysis allowed us to identify four major themes: street vending, new African migrations, discrimination and entertainment. The main findings are centered on the analysis of the representations produced by the media in particular in relation to street vending. Such representantions vary depending on the media outlet, showing different social representations of these migrants, but in most cases Senegalese migrants are portrayed in criminalizing, exoticizing or victimizing ways thus in this way, media problematises their insertion into the host society.